Analysis of the Development of Human Resource Competencies of State Civil Apparatus at the Regional Revenue Agency of Supiori Regency - Kbarek, Amelia Selfiana; Amiruddin, Amiruddin; Utami, Ayu Kurnia; Djunaedi, Djunaedi (Yayasan Gema Bina Nusantara, 2025)
This study aims to find out the development of human resource competencies of state civil apparatus at the Regional Revenue Agency of Supiori Regency. To find out the factors that become obstacles to the analysis of human resource competency development of state civil apparatus at the Regional Revenue Agency of Supiori Regency. The type of research used by the author in the research is qualitative descriptive, which is a type of research that aims to describe all types of existing conditions, be it natural phenomena or man-made events, the conditions in question can be such as forms, activities, characteristics, relationships, changes, differences, and similarities. The results of the study indicate that development of the competence of State Civil Apparatus in the Regional Revenue Agency of Supiori Regency based on the results of the study, it can be said that the development of the competence of State Civil Apparatus with indicators of Technical competence, Managerial competence, Social competence and Intellectual/strategic competence is quite good by providing study assignments and study permits, directing State Civil Apparatus to take part in education and training, attend seminars, briefings and others. However, in its implementation it is still not optimal, this is due to the obstacles that exist in the implementation process. Inhibiting factors for the development of the competence of State Civil Apparatus in the Regional Revenue Agency of Supiori Regency. include the availability of budget and lack of motivation of employees, not taking advantage of the opportunity to develop competence optimally.